Sequential, Divergent, and Cooperative Requirements of Foxl2a and Foxl2b in Ovary Development and Maintenance of Zebrafish. Issue 4 (1st April 2017) - Yang, Yan-Jing; Wang, Yang; Li, Zhi; Zhou, Li; Gui, Jian-Fang
Abstract: Foxl2 is essential for mammalian ovary maintenance. Although sexually dimorphic expression of foxl2 was observed in many teleosts, its role and regulative mechanism in fish remained largely unclear. In this study, we first identified two transcript variants of foxl2a and its homologous gene foxl2b in zebrafish, and revealed their specific expression in follicular layer cells in a sequential and divergent fashion during ovary differentiation, maturation, and maintenance. Then, homozygous foxl2a mutants ( foxl2a −/− ) and foxl2b mutants ( foxl2b −/− ) were constructed and detailed comparisons, such as sex ratio, gonadal histological structure, transcriptome profiling, and dynamic expression of gonadal development-related genes, were carried out. Initial ovarian differentiation and oocyte development occur normally both in foxl2a −/− and foxl2b −/− mutants, but foxl2a and foxl2b disruptions result in premature ovarian failure and partial sex reversal, respectively, in adult females. In foxl2a −/− female mutants, sox9a-amh / cyp19a1a signaling was upregulated at 150 days postfertilization (dpf) and subsequently oocyte apoptosis was triggered after 180 dpf. In contrast, dmrt1 expression was greater at 105 dpf and increased several 100-fold in foxl2b −/− mutated ovaries at 270 dpf, along with other testis-related genes. Finally, homozygous foxl2a −/− / foxl2b −/− double mutants were constructed in which complete sex reversal occurs early and testis-differentiation genes robustly increase at 60 dpf. Given mutual compensation between foxl2a and foxl2b in foxl2b −/− and foxl2a −/− mutants, we proposed a model in which foxl2a and foxl2b cooperate to regulate zebrafish ovary development and maintenance, with foxl2b potentially having a dominant role in preventing the ovary from differentiating as testis, as compared to foxl2a .